Nekotorye priciny i projavlenija asimmetrii dinamiceskoj struktury udarnych dejstvij - Ivanova, G. P.; Spiridonov, D. V.; Sautina, E. N. (Teorija i Praktika fiziceskoj Kul'tury, 2006)
The purposes of the work were: 1) to establish the system distinctions of dynamic structure of shock circuits proceeding from the special roles of the peripheral mechanism of control in the formation of the manual asymmetry of complex movements; 2) to show the role of the system organization of circuits in solving concrete motor tasks on the basis of the analysis of the shock actions of a different target orientation.